2021
DOI: 10.1556/446.2021.30017
|View full text |Cite
|
Sign up to set email alerts
|

Effect of wet-curing on physical properties and proteins of cured ham

Abstract: Consuming enough protein is a very important part of a balanced and healthy diet. Complete proteins are those in which all essential amino acids are present. In meat products, like hams, many different reactions occur during ageing and storage. For example, the production of free amino acids or the production of biogenic amines is formed by decarboxylation. In this study, the presence of these amino acids and biogenic amines, as well as the quality properties of cured hams during curing and ageing, were invest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 14 publications
(11 reference statements)
0
2
0
Order By: Relevance
“…Contrary to our results, in the mentioned studies no differences were either found in the curing yield and cooking loss values of groups cured in brines containing alternative or conventional sources of nitrites [ 33 , 34 ]. In the case of wet curing, the driving force for the penetration of water and other substances into or from the interior of complex cellular structure is the difference in chemical potential between meat and its surrounding brine [ 25 ]. Brine ingredients migrate into the meat and the water from the inside of the meat moves into the brine.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Contrary to our results, in the mentioned studies no differences were either found in the curing yield and cooking loss values of groups cured in brines containing alternative or conventional sources of nitrites [ 33 , 34 ]. In the case of wet curing, the driving force for the penetration of water and other substances into or from the interior of complex cellular structure is the difference in chemical potential between meat and its surrounding brine [ 25 ]. Brine ingredients migrate into the meat and the water from the inside of the meat moves into the brine.…”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, apart from dry, wet curing methods can also be distinguished. In those methods, the meat can be immersed in brine containing a given concentration of nitrite or injected with brine solution to support brine penetration [ 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%